Variability in evaluation and treatment of tibial tubercle fractures among pediatric orthopedic surgeons. Issue 2 (21st September 2021) - Fields, Michael W.; Kaushal, Neil K.; Patel, Neeraj M.; McCormick, Sekinat K.; Eberson, Craig P.; Schmitz, Michael L.; Swarup, Ishaan; Blanco, John S.; Crawford, Lindsay M.; Edobor-Osula, O. Folorunsho
Abstract : The purpose of this study was to determine the variability in clinical management of tibial tubercle fractures among a group of pediatric orthopedic surgeons. Nine fellowship-trained academic pediatric orthopedic surgeons reviewed 51 anteroposterior and lateral knee radiographs with associated case age. Respondents were asked to describe each fracture using the Ogden classification (type 1–5 with A/B modifiers), desired radiographic workup, operative vs. nonoperative treatment strategy and plans for post-treatment follow-up. Fair agreement was reached when classifying the fracture type using the Ogden classification ( k  = 0.39; P  < 0.001). Overall, surgeons had a moderate agreement on whether to treat the fractures operatively vs. nonoperatively ( k  = 0.51; P  < 0.001). Nonoperative management was selected for 80.4% (45/56) of type 1A fractures. Respondents selected operative treatment for 75% (30/40) of type 1B, 58.3% (14/24) of type 2A, 97.4% (74/76) of type 2B, 90.7% (39/43) of type 3A, 96.3% (79/82) of type 3B, 71.9% (87/121) of type 4 and 94.1% (16/17) of type 5 fractures. Regarding operative treatment, fair/slight agreement was reached when selecting the specifics of operative treatment including surgical fixation technique ( k  = 0.25; P  < 0.001), screw type ( k  = 0.26; P  < 0.001), screw size ( k  = 0.08; P  < 0.001), use of washers ( k  = 0.21; P  < 0.001) and performing a prophylactic anterior compartment fasciotomy ( k  = 0.20; P  < 0.001). Furthermore, surgeons had fair/moderate agreement regarding the specifics of nonoperative treatment including degree of knee extension during immobilization ( k  = 0.46; P  < 0.001), length of immobilization ( k  = 0.34; P  < 0.001), post-treatment weight bearing status ( k  = 0.30; P  < 0.001) and post-treatment rehabilitation ( k  = 0.34; P  < 0.001). Significant variability exists between surgeons when evaluating and treating pediatric tibial tubercle fractures.